2021
DOI: 10.3390/su132011408
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between CO2 Emissions, Air Pollution, and Tourism Flows in China: A Panel Data Analysis of Chinese Provinces

Abstract: This study quantitatively investigated the relationship between climate change (proxied by CO2 emissions), air pollution (proxied by PM2.5 concentration levels and PM10 and SO2 emissions), and tourism flows (proxied by inbound and domestic tourist arrivals) using panel data for 30 Chinese provinces from 2010 to 2017. The results demonstrate a long-term equilibrium relationship between CO2 emissions, air pollution variables, and tourism flows (including the number of inbound and domestic tourists). The panel da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 56 publications
1
6
0
Order By: Relevance
“…Zhou et al [ 34 ] show that tourists also air quality take into account when they decide where to spend their vacation. Similar results are also presented in other works [ 35 , 36 , 37 ]. All of these findings should motivate public authorities, private organizations, and individuals in a community to act on reducing air pollution.…”
Section: Literature Reviewsupporting
confidence: 92%
“…Zhou et al [ 34 ] show that tourists also air quality take into account when they decide where to spend their vacation. Similar results are also presented in other works [ 35 , 36 , 37 ]. All of these findings should motivate public authorities, private organizations, and individuals in a community to act on reducing air pollution.…”
Section: Literature Reviewsupporting
confidence: 92%
“…In addition, several studies have found that negative impacts on the environment and biodiversity are most pronounced near tourist resorts [23,24]. Some scholars have found that tourism seems to be a major contributor to greenhouse gas emissions, and its air pollution cannot be ignored [25,26]. Among the above issues, the impact on greenhouse gas emissions is an important topic of long-term academic attention.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Domestic and foreign academic circles mostly use the concentration of single or several pollutants in the air (such as PM 10 , PM 2.5 , NO 2 , SO 2 , etc.) to measure air pollution degree or air quality (Churchill et al, 2020;Zikirya et al, 2021). Considering that haze pollution has been a serious problem in China in recent years, PM2.5 concentration can better reflect the harmful impact of air pollution.…”
Section: Control Variablesmentioning
confidence: 99%